EXTRACTION ,ISOLATION AND IDENTIFICATION OF SOME ALKALOIDS COMPOUNDS FROM IRAQI MEDICINAL PLANT HALOXYLON SALICORNICUM AND STUDY ANTIHYPERGLYCEMIC EFFECT IN ALLOXAN –INDUCED DIABETIC RABBITS - Jamal Harbi Hussein Alsaadi (Basrah Journal of Veterinary Research)
The present study was carried out to determine and investigate theantihyperglycemic action of the alcoholic extract and alkaloids extracted from IraqiMedicinal Plant Haloxylon salicornicum on blood glucose level of Alloxan –InducedDiabetic Rabbits (150 mg/kg intraperitoneal) . In present study were prepared arealcoholic extract and isolated alkaloids . Preliminary qualitative tests werecarried out for all prepared extracts and identification bio active chemicals alkaloidcompounds (Acetic acid (amino carbonyl) ; 4-fluoro histamine ; hydroxyl urea; nhexylmethyl amine ; 1-methyl dodecyl amine ; Octadomine) by TLC and GC-MSchromatography . Alloxan –induced diabetic rabbits was prepared after injecting theexperimental rabbit with three dose of alloxan (I.V).Alloxan –induced diabetic rabbit, the results indicated that alcoholic extract and alkaloids extracted from Haloxylonsalicornicum showed significant decreasing in glucose conc. levels. Alkaloidsisolated from Haloxylon salicornicum showed very high activity to decrease bloodglucose levels in hyperglycemic rabbits ,where significant decreasing (P<0.05)was found at second hrs , significant decreasing (P<0.01) at fourth hr. and highsignificant decreasing (P<0.001) at sex and twenty forth hrs. Both alcoholic extractand alkaloids extracted Haloxylonsalicornicum have potential hypoglycemic effect inhyperglycemic induced rabbits